Agentenbasierte Modellierung von Landnutzungsdynamiken und Politikoptionen - Thomas Berger (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
– Agent-based modeling offers the technical opportunity to spatially integrate biophysical and socio-economic model components, thereby capturing the interactions between agricultural and environmental policy measures, land use decisions and ecological processes. Development paths in the use of resources can be calculated with the help of computer stimulations which determine the range of possible farm adjustments and policy interventions. Through coupling with global modeling systems, scenario analyses can be run to investigate the impacts of global change on land and water resources at regional and local level. This article gives an overview of agent-based modeling applied to the study of land use dynamics and policy options. It outlines an agricultural research project on agent-based, integrated modeling and concludes with a list of open questions.
Keywords: 330; Agrarboden; Agrarpolitik; Umweltpolitik; Agentenbasierte Modellierung